2011
DOI: 10.1038/pcan.2011.4
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate therapy in patients under androgen deprivation therapy for prostate cancer: a systematic review and meta-analysis

Abstract: The objective of this study was to clarify the role of bisphosphonates in the treatment of osteoporosis in patients with prostate adenocarcinoma under androgen deprivation therapy (ADT). The Medline, EMBASE, Cancerlit and the American Society of Clinical Oncology abstract databases were searched for published randomized, placebo-controlled trials evaluating the usage of bisphosphonates in patients with prostate cancer (PC) under ADT. The outcomes assessed were fracture, osteoporosis, incidence of adverse event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 39 publications
2
26
0
3
Order By: Relevance
“…Furthermore, there are concerns surrounding the overall safety of antiresorptive therapy with adverse effects such as flu-like symptoms, hypercalcaemia and hepatic failure reported in men treated with ADT. 73 Finally, as antiresorptive therapy has no effect on other key fracture risk factors, such as muscle strength, muscle mass, balance and gait, all of which are associated with an increased risk of falls and fracture, independent of BMD, alternative or adjunct interventions should be made available to patients currently undergoing ADT (Table 4). …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there are concerns surrounding the overall safety of antiresorptive therapy with adverse effects such as flu-like symptoms, hypercalcaemia and hepatic failure reported in men treated with ADT. 73 Finally, as antiresorptive therapy has no effect on other key fracture risk factors, such as muscle strength, muscle mass, balance and gait, all of which are associated with an increased risk of falls and fracture, independent of BMD, alternative or adjunct interventions should be made available to patients currently undergoing ADT (Table 4). …”
Section: Methodsmentioning
confidence: 99%
“…64,72 Administration of denosumab and zole-dronic acid decrease the rates of skeletal-related events (pathological fractures, bone pain, need for radiation or surgery for bone metastasis or spinal cord compression) and is recommended in the case of skeletal metastasis. 73,74 In patients with non-metastatic castration-resistant prostate cancer (CRPC) and with PSA doubling times of less than 6 months, treatment with denosumab delayed the occurrence of bone metastasis by 7.2 months (HR 0.77; P = 0.006). 75 …”
Section: Radiotherapymentioning
confidence: 99%
“…(51, 52) Consistent with these individual studies, a recent systematic review and meta-analysis of bisphosphonate therapy in men undergoing ADT for prostate cancer, which included 15 studies and 2634 subjects, concluded that bisphosphonate therapy significantly reduced both fracture risk [relative risk (RR) 0.80; P < 0.01] and osteoporosis (RR 0.39; P < 0.001), with zoledronic acid having the greatest effect among the bisphosphonates. (53)…”
Section: Prostate Cancermentioning
confidence: 99%